Gastric IgG4-Related Autoimmune Fibrosclerosing Pseudotumour: A Novel Location. (1st November 2010) - Rollins, Katie E.; Mehta, Samir P.; O'Donovan, Maria; Safranek, Peter M.
Abstract : We describe the first reported case of an IgG4-related autoimmune fibrosclerosing pseudotumour located in the stomach of a 75-year old woman presenting with weight loss and vomiting. A lesion was detected in the gastric body at endoscopy. Subsequent characterisation by CT was suggestive of a gastrointestinal stromal tumour. Following laparoscopic resection, the patient recovered uneventfully. Histological examination of the resected specimen revealed an IgG4-related fibrosclerosing pseudotumour, a novel location for this histopathological entity.